The Laywoman Project : Remaking Catholic Womanhood in the Vatican II Era - Henold, Mary J., 1974- (Book collections on Project MUSE., 2020)
"Summoning everyday Catholic laywomen to the forefront of twentieth-century Catholic history, Mary J. Henold considers how these committed parishioners experienced their religion in the aftermath of Vatican II. This era saw deep disturbances and reforms in the heavily paternal religious faith-at the same time as an American feminist revolution caught fire. Who was the Catholic woman for a new era?"--